Containment Amerika Serikat terhadap Fenomena Rise of China dalam Perspektif Hegemoni Realisme - Ary Arseno (Universitas Airlangga, 2019)
This paper explains about the United States’ containment strategy towardChina, the argue that the United States’ strategy of containment aimsto contain the China’s rise phenomenon. After the Cold War, China hasdeveloped as a powerful country which has capability to threaten theUnited States’ ‘sole hegemon’ status. Containment is the chosen strategy tokeep Washington at the top of the hierarchy of international system. Theauthor divide this paper into three sections, the first show the relationsthe United States builds to make containment works. Then in the sectiontwo, the author explain the United States’ containment strategy withJohn Mearsheimer’s offensive realism theory. The last section, I end thispaper with conclusion that consists of important points of the paper.